The DESCRIPTION OF LACTATION MANAGEMENT BEHAVIOR AMONG BREASTFEEDING MOTHERS 0-6 MONTHS AT SUDIANG RAYA HEALTH CARE CENTER CITY OF MAKASSAR IN 2020: GAMBARAN PERILAKU MANAJEMEN LAKTASI PADA IBU MENYUSUI 0-6 BULAN DI WILAYAH PUSKESMAS SUDIANG RAYA KOTA MAKASSAR TAHUN 2020 - ISMAIL, DWI YUNIATY; Citrakesumasari; Virani, Devintha; Syam, Aminuddin; Bahar, Burhanuddin (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2022)
Introduction: Several studies have shown that most of the obstacles for mothers when doing lactation management are due to the lack of knowledge about breastfeeding, especially exclusive breastfeeding, which can affect the attitudes and actions/implementation of mothers towards lactation management behavior. One study showed by Ibrahim, et al. (2014) showed that respondents had poor knowledge, attitudes and practices of lactation management (77.2%). The study aimed to describe the lactation management behavior among breastfeeding mothers 0-6 months in Sudiang Raya Health Care Center City of Makassar. Methods: This research was descriptive with 89 sample size mothers 0-6 months chosen by simple random sampling using questionnaire (google form). Data analysis was performed univariate using the SPSS program in frequency distribution from each variable. Result: The results showed that out of 89 respondents, 58 respondents (65.2%) had a good knowledge of lactation management, 28 respondents (31.5%) were in the sufficient category and 3 respondents (3.4%) were in the poor category. And then, from 89 respondents, all respondents had a positive attitude in terms of lactation management (100%). For the practices/actions out of 89 respondents, 58 respondents (65.2%) had good lactation management practices, 30 respondents (33.7%) were in the sufficient category and 1 respondent (1.1%) was in the poor category. Conclusions: The knowledge, attitudes and practices of lactation management among breastfeeding mothers in the work area of the Sudiang Raya Health Care Center City of Makassar in 2020 are mostly in the good category (>60%) Recommendation: Increase knowledge by adding some information about how to do lactation management in a proper way, especially in terms of techniques and breastfeeding positions, which is in practice we found there are still many mothers whose poor category in that part. Keywords: lactation management, breastfeeding mother, knowledge, attitude, practice